Multi-node distance measurement using LoRa technology: a study on the relationship between RSSI and range - Embong, Norlia; Abdullah, Norzilawati; Ambak, Zulkifli (Southeast Asian Journal of Technology and Science, 2024)
Distance is a significant factor in many smart cities, smart agriculture, and smart environment applications of the Internet of Things (IoT). LoRa, which is a Long-Range technology, low-power, is mainly employed in the IoT networks for distance measurement. On the other hand, the relationship between the Received Signal Strength Indicator (RSSI) and the distance range in the multi-node configuration using LoRa technology based on distance measurement is still being studied. The subject of the experimental research paper is the LoRa technology, which concerns distance measurement and the impact of the modulation scheme. The tests show that the RSSI values drop exponentially with the increase in distance while the Spread Factor (SF) 12 modulation scheme is being used. Besides that, the other results show the distance measurement of LoRa-based wireless communication can be increased up to 1 km with a minimum RSSI value of -120 dBm.